Social functioning violation in patients with paranoid schizophrenia and concomitant somatic and neurologic pathology - Pidkorytov, Valerii; Baibarak, Natalia (ScienceRise: Medical Science, 2017)
The aim was to determine the features of social functioning violation in patients with paranoid schizophrenia and concomitant somatic and neurologic disorders under the influence of neuroleptic treatment and to estimate psychopharmacotherapy efficiency. It is known that patients with schizophrenia often suffer from concomitant somatic pathology. Schizophrenia course, negative symptoms and cognitive disorders may prevent timely treatment and mental health care for patients with paranoid schizophrenia and concomitant somatic and neurologic disorders. Methods. According to the specially designed criteria, the main group with paranoid schizophrenia diagnosis (F 20,0) having somatic and neurologic disorders was determined according to the ICD-10 criteria. Results. On the basis of the obtained results analysis, it should be mentioned, that patients with paranoid schizophrenia and concomitant somatic and neurologic pathology will probably have poor physical and mental health. Thus, stressful events in life of patients with paranoid schizophrenia worsens somatic health and reduces adaptive potential, which in turn affects all areas of personal communication and general quality of life. Conclusion. The features of the concomitant somatic and neurologic pathology influence on social activity and quality of life of patients with paranoidal schizophrenia before and after treatment